Dating Zircons in Rocks - An EBSD Problem? - Trimby, P.; Reddy, Steven; Timms, Nicholas Eric; Kinny, Peter; Buchan, Craig; Blake, K.; Cayzer, N.; Hinton, R. (Oxford Instruments, 2006)
The field of rock dating, known as geochronology, is very important within the Earth Sciences. The ability to measure accurately the age of a rock allows a geologist to build up a clear picture of a rock's history. Not only can this provide the rock's age, but it can also give information about the pressure and temperature (PT) history and the timing of episodes of deformation.However, geochronology is not an easy subject: extracting dates from a rock sample using any number of analytical techniques is very easy, but being certain of the validity of such dates and of the process to which they relate is very difficult. It is especially problematical in the field of Archaen geology - that is, the study of some of the oldest rocks on Earth (older than 2.5 billion years old); here, determining whether a date applies to the original rock's (or mineral's) formation or some later thermal or deformation event can be impossible.There are a number of ways of dating rocks, but the 2 that are most commonly used, at least for older rocks, are Uranium-Lead and Argon-Argon (or Potassium-Argon) radiometric techniques. These techniques use the ratios between specific radiogenic isotopes to determine the age of the rock, and are usually accurate to within a few millions of years (not bad if a rock is 3,200 million years old!). Usually the minerals in which these isotopes are found are firstly imaged in an SEM using backscattered electron (BSE) or cathodoluminescence (CL) detectors to look for chemical discontinuities or zoning. The nature of the chemical variations can show whether the mineral is of primary magmatic origin (i.e. the preserved structure originated when the mineral crystallised from a molten rock body) or whether it has been subsequently altered by either a metamorphic event (with elevated temperature and / or pressure) or a deformation event. In the simplest cases, the differences between the original mineral and one that has been altered are very pronounced: this is illustrated by the variations in CL signal in 2 zircon (ZrSiO4) grains in figure 1. The concentric zoning in (a) is attributed to the grain's formation inside a magma chamber, whereas the more complex variations in (b)indicate later metamorphic alteration.